The dependence of intrinsic alignment of galaxies on wavelength using KiDS and GAMA - Georgiou, Christos; Johnston, Harry; Hoekstra, Henk; Viola, Massimo; Kuijken, Konrad; Joachimi, Benjamin; Chisari, Nora Elisa; Farrow, Daniel J.; Hildebrandt, Hendrik; Holwerda, Benne W.; Kannawadi, Arun (Astronomy and astrophysics (Berlin), 2019)
The outer regions of galaxies are more susceptible to the tidal interactions that lead to intrinsic alignments of galaxies. The resulting alignment signal may therefore depend on the passband if the colours of galaxies vary spatially. To quantify this, we measured the shapes of galaxies with spectroscopic redshifts from the GAMA survey using deep gri imaging data from the KiloDegree Survey. The performance of the moment-based shape measurement algorithm DEIMOS was assessed using dedicated image simulations, which showed that the ellipticities could be determined with an accuracy better than 1% in all bands. Additional tests for potential systematic errors did not reveal any issues. We measure a significant difference of the alignment signal between the g, r and i-band observations. This difference exceeds the amplitude of the linear alignment model on scales below 2 Mpc h−1. Separating the sample into central/satellite and red/blue galaxies, we find that the difference is dominated by red satellite galaxies.